Role Play as a Pedagogical Strategy for Cultivating Empathy - Biju Bahuleyan; Rose Babu; Aruna Davis; Shilpa AV; Sreeja CK; Archana S; Neenu Elsin Thomas; Tereesa Shojan (GAIMS Journal of Medical Sciences)
Background: Empathy is considered as the cornerstone of exemplary patient care and training medical graduates in empathy is the most challenging task for the medical educators. The traditional teaching method lacks strength in implementing this skill into the receivers.